Increase Weight Infant With Family Approach Through Massage Therapy - Sri Handayani; Rasumawati Rasumawati (Humanistic Network for Science and Technology (HNST), 2018)
The positive effects of massage or touch on the growth process of children has long been known to mankind. Touch and massage given the mother is a form of communication that can build closeness with the baby's mother. This study aimed to find out the differences baby weight before and after the massage. The population in this study were infants aged 0-12 months by taking the sample using quota sampling technique with a sample of 30 infants. Quantitative Research Methods quasi non-randomized approach experiment with pre and posttest design with one group. The study was conducted at the health center region of South Tangerang. Analysis of the test data using an independent t-test, correlation, and linear regression analysis through methods best subset. The results obtained by the average age of the baby is 5.5 months, maternal age was 28 years and 3 months, most mothers do not work as many as 21 people, maternal weight was 52.8 kg, the mean difference in weight before and after massaged in the intervention group was 0.80 kg. In the analysis of infant massage multivariate unknown variables significantly to the increase in weight with P value = 0.0001. Confounding variable is the age of the baby and the mother worked with R 2 coefficient of determination (R square) = 0.546, meaning that the variable can explain variations baby massage the baby's weight at 54.6% and the rest is explained by other variables. Conclusion The increase in weight babies are massaged higher compared with not a massage, it is advisable for the mother can do massage continuously and invite family, especially her husband to come home do baby massage, and can be used as a midwife in implementing the program in the community practice.Keywords: Baby massage, Baby weigth